Does Viewing Explain Doing? Assessing the Association Between Sexually Explicit Materials Use and Sexual Behaviors in a Large Sample of Dutch Adolescents and Young Adults. (26th April 2013) - Hald, Gert Martin; Kuyper, Lisette; Adam, Philippe C.G.; de, John B.F.
Abstract Introduction Concerns have been voiced that the use of sexually explicit materials (SEMs) may adversely affect sexual behaviors, particularly in young people. Previous studies have generally found significant associations between SEM consumption and the sexual behaviors investigated. However, most of these studies have focused on sexual behaviors related to sexually transmitted infections or sexual aggression and/or failed to adequately control for relevant covariates. Thus, research more thoroughly investigating the association between SEM consumption and a broader range of sexual behaviors is needed. Aims The study aims to investigate SEM consumption patterns of young people, and to assess the strength of the association between SEM consumption and a range of sexual behaviors, controlling for a comprehensive array of variables previously shown to affect these relationships. Methods Online cross‐sectional survey study of 4, 600 young people, 15–25 years of age, in The Netherlands was performed. Main Outcomes Measures The main outcome measures were self‐reported SEM consumption and sexual practices. Results The study found that 88% of men and 45% of women had consumed SEM in the past 12 months. Using hierarchical multiple regression analyses to control for other factors, the association between SEM consumption and a variety of sexual behaviors was found to be significant, accounting for between 0.3% and 4% of the total explained variance in investigated sexual behaviors. Conclusions This study suggests that, when controlling for important other factors, SEM consumption influences sexual behaviors. The small to moderate associations that emerged between SEM consumption and sexual behavior after controlling for other variables suggest that SEM is just one factor among many that may influence youth sexual behaviors. These findings contribute novel information to the ongoing debates on the role of SEM consumption in sexual behaviors and risk, and provide appropriate guidance to policy makers and program developers concerned with sexual education and sexual health promotion for young people. Hald GM, Kuyper L, Adam PCG, and de Wit JBF. Does viewing explain doing? Assessing the association between sexually explicit materials use and sexual behaviors in a large sample of Dutch adolescents and young adults. J Sex Med 2013;10:2986–2995.